Multimodel and neural emulators for non-linear systems: application to an indirect adaptive neural control. (19th December 2012) - Bahri, Nesrine; Atig, Asma; Abdennour, Ridha Ben; Druaux, Fabrice; Lefebvre, Dimitri
This work investigates an uncoupled multimodel emulator for non-linear system control design. Efficiency of the proposed multimodel emulator is illustrated by comparison with the neural one by their application to SISO indirect adaptive neural control. Neither an initialisation parameter and nor online adaptation is required for multimodel emulator unlike the neural one. The effectiveness of the proposed multimodel emulator is shown through numerical simulations. The obtained results using multimodel emulator are far better than neural emulator.